A Web-Based Platform to Collect Data from ESRD Patients Undergoing Dialysis: Methods and Preliminary Results from the Brazilian Dialysis Registry - Jocemir R. Lugon; Pedro A. Gordan; Fernando S. Thomé; Antonio A. Lopes; Yoshimi J. A. Watanabe; Carmen Tzanno; Ricardo C. Sesso (International Journal of Nephrology)
Introduction. The methods and initial results of a web-based platform to collect data from patients receiving maintenance dialysis in Brazil are reported. Methods. Companies providing management software for dialysis centers adapted their system to comply with a formulary of the Brazilian Society of Nephrology. Baseline and follow-up individual patients’ data were transmitted via Internet on monthly bases to the coordinating center from 2011 to 2017. Results. 73 dialysis centers provided information of 24,930 patients: 57% were male, 28% were 64 years old or older, and 13% were overweight/obese. Median dialysis vintage was 28 months. Hemodialysis was the most frequent initial therapy (93%) with venous catheters used in 64% of cases. Conventional hemodialysis remained the main current therapy (90%). Seropositivity for hepatitis C, hepatitis B, and HIV was 2.7%, 1.1%, and 0.5%, respectively. Erythropoietin (53.9%), iron (35.1%), and sevelamer (23.4%) were the most used medications. Hemoglobin < 100 g/L and serum P > 1.74 mmol/L were present in 33.1% and 36.6% of the cases, respectively. The 5-year survival of incident cases (n=7,538) was 57%. Conclusion. The initiative represents an innovative strategy to collect clinical and epidemiologic data of dialysis patients which may be applied to other settings and provides information that can contribute to guiding clinical practice and health care policy.